Penerapan model pembelajaran problem based learning (pbl) untuk meningkatkan keterampilan pemecahan masalah soal cerita bangun datar pada peserta didik kelas iii sd - Laelin Yunita Sari; Chumdari Chumdari; Anesa Surya (Didaktika Dwija Indria, 2019)
Abstract. The objective of this research are improve problem solving skills mathematic in stories matter of plane geometry by applyying the Problem Based Learning (PBL) model. This research in Classroom Action Research with three cycles. The subject of this research were students of III class at SD N 1 Kedaleman Wetan Kebumen in the 2018/2019 academic year, totalling 26 students. The research uses data collection techniques were interview, observations, tests, and documentation. The data analysis in this research are source trangulation, technique triangulation, and content validity. Result of thorough were in the intitial conditions of problem solving skills of III class students showed 15,38% clasically. The first cycle began with the first learning resulting in a percentage of 26,93% in classial, the second learning was 42,31% in classical. The second cycle began with the first learning resulting in a percentage of 53,85% in classical, the second learning was 61,54% in classical. The study continued with third cycle with the percentage of  achivement at the first learning amounting 76,92% in classical, and the second learning was 88,46% in classical terms.